Outstanding feasibility of spleen stiffness measurement by 100‐Hz vibration‐controlled transient elastography - Zhang, Xiaofeng; Wang, Haiyu; Xie, Xinpeng; Song, Jiankang; Zhang, Yuanjian; Zhou, Damei; Wu, Qiaoping; Tai, Jiaoyu; Huang, Jing; Cheng, Xiao; Li, Junying; Gu, Yixiu; et al. (JGH open, 2023)
This novel spleen‐dedicated FibroScan has high success rate and is easy to operate. The spleen stiffness is correlated with liver stiffness, which reflects the liver fibrosis stage. However, whether SSM is able to reflect the severity of liver disease warrants further observation.